Race/Ethnic Differences in Nonresident Fathers’ Involvement after a Nonmarital Birth - Ellerbe, Calvina Z. (Soc Sci Q, 2018)
OBJECTIVES: This article examines how the levels of nonresidential father involvement (over child ages 1 to 9) differ by race/ethnicity (comparing White, Black and Hispanic fathers), and then considers how individual and couple characteristics may ‘account for’ any observed differences. METHOD: Data from the Fragile Families and Child Wellbeing Study (N = 2,447) and random effects models were used to examine how nonresidential father involvement (with respect to time, engagement, shared responsibility, and coparenting with mothers) is differentiated by race and ethnicity. RESULTS: Overall, Black nonresident fathers were significantly more likely to spend time and engage in activities with their children as compared to Hispanic fathers—but not White fathers. Black fathers also shared responsibilities more frequently and displayed more effective coparenting than Hispanic and White fathers. CONCLUSIONS: Fathers’ involvement with children is shown to differ across major race/ethnic groups, with implications for children as well as for future research and public policy.